2011
DOI: 10.1299/jmmp.5.44
|View full text |Cite
|
Sign up to set email alerts
|

Using Electrical Resistance Change to Monitor the Damage in a Thick CFRP Plate Caused by a Dent

Abstract: An impact load on a thick carbon fiber reinforced plastic (CFRP) plate usually causes a dent. The dent results in a decrease of electrical resistance. Our previous paper demonstrated the effect of the dent in the measurement of electrical resistance change of a thick CFRP plate subjected to impact loading. The present paper focuses on the electrical resistance decrease caused by the dent. Numerous FEM analyses were performed, and the relationship between electrical resistance changes and delamination location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Because the method does not require additional sensors, it is applicable to existing CFRP structures. The self-sensing method using electrical resistance change has been applied to detect damage in CFRP structures by many researchers (1)- (20) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the method does not require additional sensors, it is applicable to existing CFRP structures. The self-sensing method using electrical resistance change has been applied to detect damage in CFRP structures by many researchers (1)- (20) .…”
Section: Introductionmentioning
confidence: 99%
“…For a thick CFRP plate, however, the delamination cracking is accompanied by a dent on the surface and the dent caused a decrease in the electrical resistance in the thickness direction of the CFRP plate (17) . The authors' group has revealed a dent monitoring process using the decreased electrical resistance caused by the dent (20) . The mechanism by which the dent reduces the electrical resistance in the thickness direction of the CFRP plate, however, has not been clarified.…”
Section: Introductionmentioning
confidence: 99%